2017
DOI: 10.1038/s41598-017-16633-6
|View full text |Cite
|
Sign up to set email alerts
|

A meta-proteomics approach to study the interspecies interactions affecting microbial biofilm development in a model community

Abstract: Microbial biofilms are omnipresent in nature and relevant to a broad spectrum of industries ranging from bioremediation and food production to biomedical applications. To date little is understood about how multi-species biofilm communities develop and function on a molecular level, due to the complexity of these biological systems. Here we apply a meta-proteomics approach to investigate the mechanisms influencing biofilm formation in a model consortium of four bacterial soil isolates; Stenotrophomonas rhizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 70 publications
1
31
0
1
Order By: Relevance
“…This environment for water contaminated with 30 different agrochemicals and with physicochemical conditions unfavorable to the survival of microorganisms identified in this work was considered stressful (Table 1 and S1 Table). The organization of bacteria in biofilms in tanks and containers, with their cooperative or antagonistic interactions, may lead to a specific combination of species with increased adaptability to the environment [49]. Thus, the most dominant sequences in B2, corresponding to the genera Enterobacter and Acinetobacter , are poorly represented in the other communities studied, including the biofilms in B1, G1 and G2 (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…This environment for water contaminated with 30 different agrochemicals and with physicochemical conditions unfavorable to the survival of microorganisms identified in this work was considered stressful (Table 1 and S1 Table). The organization of bacteria in biofilms in tanks and containers, with their cooperative or antagonistic interactions, may lead to a specific combination of species with increased adaptability to the environment [49]. Thus, the most dominant sequences in B2, corresponding to the genera Enterobacter and Acinetobacter , are poorly represented in the other communities studied, including the biofilms in B1, G1 and G2 (Fig 2).…”
Section: Resultsmentioning
confidence: 99%
“…Proteomics provides valuable data in the field of microbiology; proteomics characterizes the molecular model systems to investigate specific aspects of microbiological gene expression and metabolism. In medical microbiology, these data help to analyze the disease mechanism and how the pathogen interact with their hosts; these investigations are largely focused on the development of novel approaches for treatment and prevention of infectious diseases (Herschend et al, 2017;Wang et al, 2016).…”
Section: Role Of Maldi-tof-in Diagnosismentioning
confidence: 99%
“…Work on this community has established that co-cultivation leads to enhanced biofilm formation, that all four species increase in cell counts through biofilm co-cultivation and that all four species are indispensable for the synergy to occur (31). Later studies has hinted that the synergy can be linked to a specific spatial organisation of community members during co-cultivation in biofilms (32), and meta-transcriptomics (33) and - proteomics (34) studies have identified amino acid cross-feeding as a potential driver for the synergy. However, the impact of the community on its surrounding environment, and the mutual community-environment interplay, has not been explored.…”
Section: Introductionmentioning
confidence: 99%